Analisis Penggunaan Mobile Banking pada Generasi Milenial dengan Pendekatan Technology Acceptance Model (TAM) - Lutfi Rokhiyatul Mu'asiroh; Darwanto Darwanto (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2021)
This research aims to analyze the factors that can influence the millennial generation in using mobile banking. The approach in this research uses the Technology Acceptance Model (TAM) that has been developed by Davis (1989), namely benefits and convenience, and by adding three external variables, namely security, experience and compatibility . The research model was empirically tested using survey data from the millennial generation of students at Diponegoro University. The result of the analysis shows that all constructs in the TAM model namely benefits, convenience and the three external variable, security, experience and compatibility have a positive and significant effect on the use of mobile banking in the millennial generation partially or simultaneously.  The implication of the results of this research is relevant for the millennial generation to be more confident on using mobile banking that can simplify their banking activities.